Correlation Based Clustering of the Amman Stock Exchange - Abdoh, Hussein A. (International Journal of Economics and Financial Issues, 2017)
This study classifies firms listed on Amman Stock Exchange (ASE) into clusters based on Pairwise stock correlations. The partitioning level technique is based on the decrease in firms' concertation in their clusters when one additional cluster is created. The results indicate that five and nine clusters lower the concentration significantly and thus are selected as the grouping levels. The concentration of firms in some clusters is very low while the concentration in other clusters is very high. The clustering outcome indicates that ASE could be characterized by high R square and return synchronicity. Keywords: Clusters, pairwise return correlations, Diversification. JEL Classifications: G10, G11, M21